Ceria doping boosts methylene blue photodegradation in titania nanostructures. (22nd April 2021) - Alberoni, Chiara; Barroso-Martín, Isabel; Infantes-Molina, Antonia; Rodríguez-Castellón, Enrique; Talon, Aldo; Zhao, Haiguang; You, Shujie; Vomiero, Alberto; Moretti, Elisa
Abstract : The photocatalytic activity of titania nanotubes and nanoparticles toward methylene blue (MB) can be enhanced through addition of a small amount of Ce. MB acts as a hole scavenger, fastening the photocatalytic process. Abstract : Ceria-doped titania photocatalysts (ceria loading 0.25–5.0 wt%) were synthesized by hydrothermal methods for water remediation. Nanotubes (CeTNT x ) and nanoparticles (CeTNP x ) were obtained. Ceria doping was applied to tune the electronic properties of nanostructured titania, boosting its photocatalytic activity. CeTNT nanostructures contained anatase as the only titania phase, whereas the CeTNP series consisted of both anatase and rutile polymorphs. The Ce addition induced a decrease in the energy gap, allowing enhancement of visible light harvesting. The photodegradation of methylene blue, MB, in aqueous solution was chosen to study the influence of the morphology and the ceria loading on the photocatalytic response, under UV and solar light. Both CeO2 –TiO2 nanoparticles and nanotubes were found to be very active under UV light. The highest MB degradation rates were obtained for the 0.25 wt% CeO2 doping, for both nanotubes and nanoparticles (0.123 and 0.146 min −1, respectively), able to photodegrade completely the dye after 120 min. The two samples are stable after a 3-cycle reusability test. The photo-response under simulated solar light confirmed that doping titania with ceria allows harvesting visible light absorption, enhancing its photoactivity. A maximum efficiency of 85% under simulated sunlight at a degradation rate of 0.054 min −1 was obtained. Transient photoluminescence confirmed that MB acts as a charge scavenger for the composite system. These results pointed out ceria-doped titania nanostructures as a promising class of photocatalysts for the degradation of dyes and other hazardous organic compounds in wastewater.